Pengelolaan Karya Inovasi Mahasiswa dan Dosen Berbasis Website di Perpustakaan Universitas Surabaya - Bambang Septiawan; Kristina; Amirul Ulum; Achmad Basori (Media Informasi, 2026)
The advancement of information technology has brought significant changes to the way higher education institutions manage innovative works. Students and lecturers, as the main actors in academic and research activities, require an organized system to document and disseminate their works optimally. Many high-value innovations remain inadequately documented, putting them at risk of being underrecognized or even lost. To address this issue, the library has developed a web-based innovation management system called GEMILANG-IN (GEnerasi MIlenial with Innovative Steps). This system is designed as a platform for archiving, managing, and publishing innovative works produced by the academic community in a structured and sustainable manner. This study provides a comprehensive review of the foundation, objectives, implementation methods, and benefits of GEMILANG-IN in supporting increased visibility of innovative works, digital preservation, and ease of access. Through this program, the university is expected to present itself as a productive, innovative, and competitive institution at both national and global levels.